Investigation of the Physical Properties of a Fabric with a Conductive Fibre - Sacevičienė, Virginija; Klevaitytė, Ramunė; Radavičienė, Svetlana; Urbelis, Virginijus (Jaunųjų mokslininkų darbai, 2021)
The aim of this work is to investigate physical and mechanical performance of fabrics with a conductive fibre after washing conditions. Three commercially available fabrics with a conductive fibre and one fabric without a conductive fibre were chosen as a research object. The physical properties of the fabrics were evaluated by the loss of the mechanical performance, changes in structure and magnetic permeability. Fabric elasticity and thickness decrease after washing, except for the fabric without a conductive fibre. Magnetic field permeability of all fabrics decreases after washing. The properties of the fabric with a conductive fibre woven in one direction change the most, its magnetic field permeability is the greatest. In all cases magnetic field permeability at the seam is lower than in separate pieces of the fabric. The highest frequency of the fabric with a thread woven in both directions is at the seam but in all cases the frequencies of separate pieces of fabrics are lower. Tests showed that the best dielectric properties are of the fabric with conductive yarn woven in the weft direction and the highest capacitance change of which is ΔC=74,79%.